Analysis of The Effect of Job Satisfaction, Organizational Supports, and Leadership Style on Work Motivation in Improving Employee Performance - Nurjeny Ernawati; Ferryal Abadi (Eduvest - Journal of Universal Studies, 2024)
Purpose – The service sector is a business that prioritizes trust, so client satisfaction is the main thing. Improving the quality of services provided by the company can encourage the achievement of business success now and in the future. Methodology –To answer the objectives set in this research, an online electronic questionnaire was used as a tool to collect data relating to the variables, which were distributed to 210 back-office employee respondents of Holding Company. The collected data is then processed using the SEM test. Findings – six hypothetical conclusions can be drawn, namely that it is proven that job satisfaction, organizational support, and leadership style have a positive and significant effect on employee work motivation. It is proven that work motivation, job satisfaction, and leadership style have a positive and significant effect. Originality – Previous research discussed job satisfaction, organizational culture, leadership style, work motivation, and employee performance. The research's aim, based on the research gap above, is to explain how job satisfaction, organizational support, and leadership style influence work motivation in improving employee performance.